Nigeria, a country under siege : issues of conflict and its management /edited by Dele Babalola and Hakeem Onapajo. - Babalola, Dele; Onapajo, Hekeem (Cambridge Scholars Publishing, 2018)
This volume offers a comprehensive assessment of the problem of conflict and its methods of management in Nigeria's contemporary democracy. It represents a compendium of resourceful studies provided by experts on conflict studies from various disciplines across the Social Sciences and Humanities. Such studies are very useful at this crucial point in Nigeria's history as there are currently various national and international efforts to address the scourge of violent conflicts that have caused huge numbers of deaths and displacement of persons. The book will be of particular interest and use to.